2016
DOI: 10.1371/journal.pone.0155324
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Liver Decellularization Maintains Extracellular Matrix Micro-Architecture and Composition Predisposing to Effective Cell Seeding

Abstract: Hepatic tissue engineering using decellularized scaffolds is a potential therapeutic alternative to conventional transplantation. However, scaffolds are usually obtained using decellularization protocols that destroy the extracellular matrix (ECM) and hamper clinical translation. We aim to develop a decellularization technique that reliably maintains hepatic microarchitecture and ECM components. Isolated rat livers were decellularized by detergent-enzymatic technique with (EDTA-DET) or without EDTA (DET). Hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 39 publications
(90 reference statements)
2
75
0
1
Order By: Relevance
“…Morphologically, our decellularized kidney preserved the glomerulus and its vascular network upon examination with H&E and SEM. It was reported that high concentrations of SDS (1%) and Triton‐x cause destruction of the vascular network of rat livers during decellularization process, which makes the scaffolds unsuitable for potential transplantation . Importantly, we have shown the maintenance of the vascular network.…”
Section: Discussionmentioning
confidence: 54%
“…Morphologically, our decellularized kidney preserved the glomerulus and its vascular network upon examination with H&E and SEM. It was reported that high concentrations of SDS (1%) and Triton‐x cause destruction of the vascular network of rat livers during decellularization process, which makes the scaffolds unsuitable for potential transplantation . Importantly, we have shown the maintenance of the vascular network.…”
Section: Discussionmentioning
confidence: 54%
“…PHH is the best cell model for HBV studies. [22][23][24] The advantages of decellularization liver scaffold are obviously. Advanced 3D liver models aimed at recreating hepatocyte physiological function have been established and believed to be promising in field such as regeneration and drug screening.…”
Section: Discussionmentioning
confidence: 99%
“…Liver cirrhosis is accompanied by abnormal changes in ECM structure and composition (Klaas et al, ), remodeling in the ECM composition may alter cell signaling and facilitate liver regeneration for liver diseases (Klaas et al, ; Williams, Clouston, & Forbes, ). On the other hand, the decellularization procedure without using harsh detergents may result in structural integrity of ECM (Maghsoudlou et al, ); moreover, Triton X‐100, a mild detergent and typically used for liver decellularization (Badylak, Taylor, & Uygun, ), can only reduce cell component/DNA content without depleting any glycosaminoglycans (GAGs) during the washing process (Bruyneel & Carr, ). The effect could be attributed that GAGs and other components (collagen, proteoglycans) constitute the liver extracellular microenvironment, and also play an important role in hepatic functions and viability (Damania et al, ; Lee et al, ); furthermore, the wound ECM of GaIN‐damaged cells can be subsequently replaced by mature ECM and return to the preinjury state (Jonker, Dijkhuis, Boes, Hardonk, & Grond, ).…”
Section: Discussionmentioning
confidence: 99%